Effect of Row Spacing, Seeding Rate, and Herbicide Program in Glufosinate-Resistant Soybean on Palmer Amaranth Management. (September 2015) - Bell, Holden D.; Norsworthy, Jason K.; Scott, Robert C.; Popp, Michael
Abstract : A field experiment was conducted in Fayetteville, AR, in 2012 and 2013 to determine the influence of soybean row spacing, seeding rate, and herbicide program in glufosinate-resistant soybean on Palmer amaranth control, survival, and seed production; soybean groundcover and grain yield; and economic returns. Soybean groundcover was > 80% by 85 d after soybean planting (DAP) for all row spacing and seeding rates in 2012 and in 2013 all soybean row spacings and soybean seeding rates had achieved > 90% groundcover by 50 DAP. Difference in groundcover between years was due to lack of precipitation in 2012. Palmer amaranth control at 21 DAP was 99 to 100% for both years when a PRE application of S -metolachlor plus metribuzin was made at planting. At 42 DAP, Palmer amaranth control following PRE-applied S -metolachlor plus metribuzin was ≥ 98 and ≥ 88% in 2012 and 2013, respectively. When relying on a POST-only herbicide program initiated at 21 DAP, Palmer amaranth control ranged from 52 to 84% across row spacings at 42 DAP. At soybean harvest, Palmer amaranth control was ≥ 95% in 2012 and ≥ 86% in 2013 regardless of row spacing or seeding rate when S -metolachlor plus metribuzin was applied at planting. Conversely, total-POST programs had no more than 50 and 85% Palmer amaranth control in 2012 and 2013, respectively. In both years, Palmer amaranth density and seed production at soybean harvest were generally lower in the PRE herbicide programs compared to POST-only programs. Use of a PRE herbicide at planting also improved soybean grain yield and economic returns over programs that relied on a POST-only program. Overall, the impacst of soybean row spacing and seeding rate on Palmer amaranth control, density, or seed production were less apparent than the influence of herbicide programs.